Temática vinculada con el medio hospitalario para la formación de ingenieros biomédicos - Ortiz Posadas, M. R.; Gaitán González, M. J.; Ortiz Pedroza, M. R.; Martínez Licona, F. M.; García González, M. T. (Revista Mexicana de Ingenieria Biomedica, 2001)
The knowledge related to the hospital environment plays a priority roll, not only for the engineers working within a hospital but for the professional career of any biomedical engineer. The purpose of the present work is to propose a general curriculum related to the hospital environment for biomedical engineers, as well as the particular curriculum for those professionals specializing in clinical engineering. For this purpose, a poll was applied to sixty graduates from UAM-I, while another one was given to twenty biomedical engineering departments in clinical settings. World trends in clinical engineering were also considered. All these activities contributed to defining the biomedical engineer profile that the society is requiring nowadays, orienting the required hospital-related knowledge that would result in a better professional performance of biomedical engineering graduates.